Physical activity and technology usage performed by patients with coronary artery disease: a gender approach. (2nd July 2022) - Munoz Gomez, E; Moreno-Segura, N; Sentandreu-Mano, T; Deka, P; Klompstra, L; Pathak, D; Sempere-Rubio, N; Orihuela, L; Mont, J; Cruz, M; Westas, M; Marques-Sule, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recent studies show that cardiac telerehabilitation, including exercise and lifestyle modification, is effective in reducing cardiovascular risk factors in patients with coronary artery disease (CAD). Thus, physical activity and technology usage of patients with CAD are important key points in order to create technology-based cardiac rehabilitation programs to improve physical patients´ condition and reduce cardiovascular risk. Purpose: The aim of this study was to compare the physical activity and the technological usage of women and men with CAD. Methods: A cross-sectional study in patients with CAD was performed. Sociodemographic data, physical activity (measured with the International Physical Activity Questionnaire, IPAQ) and the technology usage (measured with the Technology use subscale of the Technology Usage Questionnaire) were collected. Descriptive and inferential analyzes were performed to explore the differences between men and women with CAD. Results: A total of 70 participants were included (84.28% men, mean age=59±8.54 years). Regarding the IPAQ, men significantly reported higher walking time (99.31±95.22 METS vs. 33.28±37.42 METS, p=0.001, respectively) and higher total physical activity (4164.91±4164.91 METS vs. 1390.68±1609.05 METS, p<0.001, respectively) than women. In relation to technology usage, the entire sample used a mobile phone, whilst there were no significant gender differences in the functions/applications used (phone calls, text messages, camera, receive videos/photos, internet searches, apps, instant messages, social media, games) (p=0.068). Although the majority of the participants (85.71%) had regular access to internet, men used their phone more frequently than women (81.10% vs. 37.50%, p=0.005, respectively). Comparison by gender showed no significant differences in the type of device used for internet searches (computer, tablet, mobile phone) (p=0.169), familiarization with technology-based physical activity games (p=0.801), use of heart rate monitors (p=0.193), preference to monitor heart rate when exercising (p=0.664), nor use of other devices to monitor physical activity (pedometer, etc.) (p=0.193). Conclusion: Based on the results obtained, we conclude that men with CAD were more physical active and used the Internet more often than women, whilst there were no differences by gender in the rest of variables. Assessment of physical activity and technology usage should be implemented in patients with CAD, in order to adapt and improve the design of technology-based telerehabilitation programs